Frontline Science: HIV infection of Kupffer cells results in an amplified proinflammatory response to LPS - Mosoian, Arevik (J Leukoc Biol, 2017)
End-stage liver disease is a common cause of non-AIDS-related mortality in HIV(+) patients, despite effective anti-retroviral therapies (ARTs). HIV-1 infection causes gut CD4 depletion and is thought to contribute to increased gut permeability, bacterial translocation, and immune activation. Microbial products drain from the gut into the liver via the portal vein where Kupffer cells (KCs), the resident liver macrophage, clear translocated microbial products. As bacterial translocation is implicated in fibrogenesis in HIV patients through unclear mechanisms, we tested the hypothesis that HIV infection of KCs alters their response to LPS in a TLR4-dependent manner. We showed that HIV-1 productively infected KCs, enhanced cell-surface TLR4 and CD14 expression, and increased IL-6 and TNF-α expression, which was blocked by a small molecule TLR4 inhibitor. Our study demonstrated that HIV infection sensitizes KCs to the proinflammatory effects of LPS in a TLR4-dependent manner. These findings suggest that HIV-1-infected KCs and their dysregulated innate immune response to LPS may play a role in hepatic inflammation and fibrosis and represent a novel target for therapy.